STATUS OF IMMUNIZATION AND NUTRITION AMONG HEALTH CARE PROVIDERS' (NURSES) CHILDREN UNDER TWO YEARS OF AGE WORKING IN LIAQUAT UNIVERSITY OF MEDICAL & HEALTH SCIENCES, JAMSHORO, HYDERABAD SINDH - Zubida Chandio; Ejaz Khan; Muhammad Ibrahim Ansari et al. (Journal of University Medical & Dental College, 2018)
ABSTRACT:INTRODUCTION: Immunization is the most important and cost eﬀective strategy of World Health Organization and United Nations International Children Emergency Fund with the guidance and assisting to prevent target diseases which is often neglected that requires attention. Eﬀectiveness of vaccination is possible through the nutrition as well. MATERIAL AND METHODS: STUDY DESIGN: Cross-sectional study STUDY SITE: LUMHS Jamshoro/ Hyderabad DURATION: Oct 2016 to Mar: 2017 POPULATION & SAMPLES: Children under 24 months of health care providers (nurses) SAMPLING TECHNIQUE: Universal sampling technique SAMPLE SIZE: 100 calculated via Prevalence Rate TOOL: MUAC were computed with reference to the WHO-2007 on Anthro version 3.2.2. Cut oﬀ value of all indices between -2 and 2 SD was considered normal. Data was collected by using prestructured questionnaire partially adopted from previous study. STATISTICAL ANALYSIS: was performed on SPSS version 20.0. RESULTS: The results of study reveal overall coverage of 96 %. All the antigens have good coverage except measles II, which is around 66%. With this vaccination coverage, mostly the children have had normal nutritional status except a negligible percentage of six percent. CONCLUSION: It is concluded that the nurses in LUMHS have their children fully immunized against the VPDs but schedule of measles II vaccine is disturbed. The immunization and nutrition of their children are also comparatively better than the available ﬁgures about general population in Sindh. Education, knowledge and accessibility of a parent play a vital role in getting his/her child fully vaccinated.